Qualitative and quantitative cues in consumers' valuation of food safety: Evidence from Lebanon. Issue 3 (12th March 2019) - Chalak, Ali; Diab, Mohammad; Kassem, Issmat I.; Abiad, Mohamad G.
Abstract: In this work, we explore consumers' behavior toward the joint provision of qualitative and quantitative food safety information. To this end, we conduct a choice experiment involving a representative sample of 700 households from Beirut, Lebanon, designed around the purchase of a high risk Middle Eastern traditional street food, "shawarma." The surveyed household sample was divided among two treatments where one was provided with additional quantitative risk reduction information, hence labeled "informed" versus the other which is labeled as "uninformed". Accordingly, we compare the willingness to pay (WTP) values between both informed and uninformed respondents given typical risk reduction levels using mixed‐logit. The analysis illustrates that consumers were less likely to choose more expensive products—all else being equal—with the average consumer preferring to buy shawarma sandwiches from "round the corner" shops as opposed to walking for more than 10 min, driving or ordering delivery. However, when food safety attributes were introduced preference shifted significantly toward food safety certification in all iterations as compared to no certification. This preference is independent of whether risk reduction information was provided. Nevertheless, once quantitative risk reduction information was shared, the results revealed a decrease in preference for food safety certificates. Accordingly, our results query the validity of incomplete risk information in food safety certifications and challenge some of the implications of risk communication on consumers' choice highlighting the need for improved and well‐defined risk communication strategies. Practical applications: Based on our results, we foresee a merit for public authorities in Lebanon to review and upgrade the current food safety monitoring and certification services and couple them with assertive and well‐publicized risk reduction communication strategies. On the other hand, we suggest that the cost associated with these services should be heavily discounted or subsidized to benefit small and street food vendors. This will provide a powerful incentive for them to substantially improve on their food safety and hygiene practices. Given the evidence on the high premiums consumers are willing to pay for safer foods and transparent risk communication, such an incentive will become more persuasive for small food vendors. Accordingly, this will establish a robust market for street food safety in general and street foodborne risk communication in particular with considerable welfare gains to street food vendors which will ultimately shape consumer behavior.